Spatiotemporal dynamics and driving factors of irrigation water demands in China - Suning Fan; Tongbing Liu; Minzhong Zou; Yu Fang; Jun Niu; Shaozhong Kang (Agricultural Water Management)
China faces significant challenges due to escalating irrigation water demands and constrained water resources. However, comprehensive national-level analyses of irrigation water demands integrating multiple crops, spatial scales, and driving factors remain scarce. This study addresses this gap by examining the spatiotemporal dynamics and driving factors of irrigation water demand in China from 2000 to 2018, leveraging the Spatial Production Allocation Model (SPAM) dataset and applying the Penman-Monteith model and a multi-regional Logarithmic Mean Divisia Index (LMDI) decomposition approach. During the study period, the Net irrigation water demand (NW) peaked at 250.68 G m³ in 2013, with significant declines in the South and East but increases in the water-scarce North and Northwest. Rice dominated national NW, contributing 46–52 % of the total, while regional expansion in rice and cotton cultivation drove significant NW growth in the Northeast and Northwest. The Gross irrigation water demand (GW) exhibited a national decrease of 76.65 G m³, and the impacts of four driving factors -water saving technology, planting scale, planting patterns, and climate change - varied over time and across regions. Water-saving technology emerged as the most significant factor in reducing GW, offsetting 90.92 G m³ nationally. However, the expansion of irrigated farmland added 47.96 G m³, particularly in arid regions. Climate change exhibited regionally diverse impacts (-10.35–4.17 G m³), underscoring the need for targeted water management interventions. This study provides valuable insights for optimizing crop patterns, advancing irrigation technologies, and formulating region-specific policies to enhance agricultural water management and ensure food security in China.